Identifying s-wave pairing symmetry in single-layer FeSe from topologically trivial edge states - Wei, Zhongxu; Qin, Shengshan; Ding, Cui; Wu, Xianxin; Hu, Jiangping; Sun, Yu-Jie; Wang, Lili; Xue, Qi-Kun (Nature communications, 2023)
Determining the pairing symmetry of single-layer FeSe on SrTiO 3 is the key to understanding the enhanced pairing mechanism. It also guides the search for superconductors with high transition temperatures. Despite considerable efforts, it remains controversial whether the symmetry is the sign-preserving s - or the sign-changing s ± -wave. Here, we investigate the pairing symmetry of single-layer FeSe from a topological point of view. Using low-temperature scanning tunneling microscopy/spectroscopy, we systematically characterize the superconducting states at edges and corners of single-layer FeSe. The tunneling spectra collected at edges and corners show a full energy gap and a substantial dip, respectively, suggesting the absence of topologically non-trivial edge and corner modes. According to our theoretical calculations, these spectroscopic features can be considered as strong evidence for the sign-preserving s -wave pairing in single-layer FeSe. The nature of the pairing symmetry in superconducting single-layer FeSe has been the subject of intense debate. Here, the authors use scanning tunneling microscopy/spectroscopy to show the absence of topological edge/corner modes, providing evidence for sign-preserving s-wave pairing.